A disequilibrium compaction model constrained by seismic data and application to overpressure generation in The Eastern Black Sea Basin. (1st October 2012) - Marín‐Moreno, Héctor; Minshull, Timothy A.; Edwards, Rosemary A.
Abstract Locating and quantifying overpressures are essential to understand basin evolution and hydrocarbon migration in deep basins and thickly sedimented continental margins. Overpressures influence sediment cohesion and hence fault slip in seismically active areas or failure on steep slopes, and may drive catastrophic fluid expulsion. They also represent a significant drilling hazard. Here, we present a method to calculate the pore pressure due to disequilibrium compaction. Our method provides an estimate of the compaction factor, surface porosity and sedimentation rate of each layer in a sediment column using a decompaction model and the constraints imposed by seismic data and geological observations. For a range of surface porosities, an ad hoc iterative equation determines the compaction factor that gives a calculated layer thickness that matches the observed thickness within a tolerance. The surface porosity and compaction factor are then used to obtain a density profile and a corresponding estimate of P‐wave velocity (Vp). The selected parameters are those that give a good match with both the observed and calculated layer thicknesses and Vp profiles. We apply our method to the centre of the Eastern Black Sea Basin (EBSB), where overpressures have been linked to a low‐velocity zone (LVZ) at ca. 5500–8500 m depth. These overpressures were generated by the relatively high sedimentation rate of ca. 0.28 m ka−1 of the low permeability organic‐rich Maikop formation at 33.9–20.5 Ma and an even higher sedimentation rate of ca. 0.85 m ka−1 at 13–11 Ma. We estimate a maximum pore pressure of ca. 138 MPa at ca. 8285 m depth, associated with a ratio of overpressure to vertical effective stress in hydrostatic conditions (<inline-graphic mimetype="image" xlink:href="ark:/27927/pgg20p73b2t" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />λ*) of ca. 0.7. These values are lower than those presented in a previous study for the same area.